Концепція побудови апаратури багатопараметрового вихрострумового контролю - Тетерко, А.Я.; Гутник, В.І. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Concept of development of Eddy current apparatus for measuring plural characteristics of a test object is presented. Said concept is based on method of constructing direct and / or inverse multivariable nonlinear transformation function of an EC system. Processing of an EC sensor response with applied said function is guaranteed high accuracy of a test object characteristics measuring.